Using Model Of Sustainable Growth Rate In Evaluation Company Past Performance And Managing Company Future Direction - Soo, Yee Tein (2004)
This project is about growth and particularly about management of growth in the business firm. The ultimate aim of this project is to employ the Higgins's model of Sustainable Growth Rate to discuss about the growth of Genting Berhad in the last 10 years and its future direction.